2012
DOI: 10.1002/ibd.21725
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of small bowel disease in pediatric Crohnʼs disease on magnetic resonance enterography

Abstract: MRE in the pediatric population often demonstrates increased contrast uptake, bowel wall thickening, and perienteral lymphadenopathy in CD. More chronic small bowel changes seen commonly in adults and solitary jejunal involvements are less commonly seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This survey illustrates a degree of discrepancy among experts performing MRE. Considering the proportion agreeing on a valid indication for MRE, only two indications exceeded 80 %: the initial diagnosis and follow-up of Crohn’s disease [ 6 18 ]. Otherwise, we observed a wide variation among our experts regarding other indications for MRE.…”
Section: Discussionmentioning
confidence: 99%
“…This survey illustrates a degree of discrepancy among experts performing MRE. Considering the proportion agreeing on a valid indication for MRE, only two indications exceeded 80 %: the initial diagnosis and follow-up of Crohn’s disease [ 6 18 ]. Otherwise, we observed a wide variation among our experts regarding other indications for MRE.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact frequency of the small bowel (SB) CD is unknown, most gastroenterologists believe that its prevalence has been underestimated and that it may have an increased incidence among children and young adolescents [2] . A recent study performed in pediatric patients with magnetic resonance (MR) enterography [3] , according to previous studies [4] , confirmed that the involvement of the terminal ileum is common to more than three times compared to that of the jejunum and the rest of the ileum. Moreover, the involvement of the jejunum alone is uncommon and it is more difficult to investigate because of its tendency to stay non distended [3] .…”
Section: Introductionmentioning
confidence: 78%
“…A recent study performed in pediatric patients with magnetic resonance (MR) enterography [3] , according to previous studies [4] , confirmed that the involvement of the terminal ileum is common to more than three times compared to that of the jejunum and the rest of the ileum. Moreover, the involvement of the jejunum alone is uncommon and it is more difficult to investigate because of its tendency to stay non distended [3] . The clinical importance of the SB CD phenotype is the impact that a diffuse SB disease is expected to have on a child's growth and development.…”
Section: Introductionmentioning
confidence: 78%
“…Bowel wall thickening is the common finding of CD with sensitivity of 83%-91% and a specificity of 86%-100% at MR enterography [50] . It is defined as a bowel wall thickness measuring more than 3 mm in a distended loop and may be eccentric or concentric and smooth or nodular and several study [5,43] . Masselli et al [42] confirmed that the terminal ileum is the most common localiazation of bowel wall thickness ( Figure 2).…”
Section: Indicationsmentioning
confidence: 99%